Effects of a native and a non-native macrophyte species of Hydrocharitaceae on Chironomidae and Oligochaeta assemblages structure doi: 10.4025/actascibiolsci.v35i3.10855 - Behrend, Rômulo Diego de Lima; Teixeira, Mariana Carolina; Fernandes, Sue Ellen Prata; Camargo, Janielly Carvalho; Rosin, Gisele Cristina; Takeda, Alice Michiyo (Acta Scientiarum. Biological Sciences, 2013)
This study investigated the structure of the Oligochaeta and Chironomidae assemblages associated with monospecific stands of two submerged macrophyte species: Egeria najas and Hydrilla verticillata. Samplings were carried out in Leopoldo Backwater and Paraná river, in August 2008. To assess the structure of Oligochaeta and Chironomidae assemblage in each macrophyte we calculated: species density, richness, diversity, and evenness. A detrended correspondence analysis (DCA) was used to summarize Oligochaeta and Chironomidae assemblages composition. The highest values of species density and richness for the two groups were recorded in H. verticillata. Although there were no significant differences in density, richness and Shannon diversity, the assemblage composition of these groups was significantly different between plant species. These results suggest that despite being a recent colonizer in the upper Paraná river habitats, the non-native species H. verticillata seems to provide favorable conditions for the establishment of native assemblages of Chironomidae and Oligochaeta. Moreover, differences in the species composition of Oligochaeta and Chironomidae arose from peculiar characteristics of each plant, as attached microorganisms and organic matter, so that other factors, rather than plant architecture can also influence the assemblage of these groups.